T‐bet transcription factor in cardiovascular disease: Attenuation or inflammation factor?. Issue 6 (7th December 2018) - Haybar, Habib; Rezaeeyan, Hadi; Shahjahani, Mohammad; Shirzad, Reza; Saki, Najmaldin
Abstract: T‐bet is a major transcription factor increasing inflammatory responses in the immune system. Recently, it has been shown that this factor leads to inflammation in cardiovascular disease (CVD). In this study, we examine the dual role of T‐bet in inducing and suppressing inflammatory reactions as well as angiogenesis induction due to inflammatory cytokines in CVD. Relevant literature was identified by a Pubmed search (1992–2018) of English‐language papers using the terms "T‐bet, " "Cardiovascular disease, " "Immune response, " and "Angiogenesis." Although T‐bet causes differentiation of Th1 cells and activation of immune cells such as NK and DC, it suppresses inflammatory responses and replaces damaged vessels with new ones by activating regulatory T‐cells and stimulating angiogenesis. It can be stated that T‐bet acts as double‐edged sword. Therefore, the identification of pathways that can increase the function of T‐bet in activating Tregs and inducing angiogenesis might be used as a new therapeutic option in future investigations. HIGHLIGHTS: T‐bet factor plays an essential role in the regulation of immune responses in CVD. T‐bet factor induces angiogenesis through the mediation of inflammatory cytokines. T‐bet can be effective in CVD pathogenesis via interaction with other transcription factors. Abstract : This manuscript attempts to discuss effect of T‐bet on function of immune cell in cardiovascular disease. Also we evaluation of relationship between T‐bet and angiogenesis by inflammatory cytokine and endothelial progenitor cells.